Responsibility in the post-crisis organizations: strategic shifts in internal communication for sustainable and resilient organizational culture - Cvikl Postružnik, Natalie; Lesar, Nina; Buček, Tjaša-Ana (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2025)
Purpose of the article: This paper explores the evolving role of coaching as an internal communication tool in advancing responsibility as part of public relations goals, particularly in the post-crisis era.Originality/Value: By revisiting and upgrading a study initially conducted in 2019, the study specifically investigates how coaching is currently integrated into internal communication practices in Slovenian organizations, its influence on enhancing personal and organizational responsibility, its role in alignment with sustainability strategies, and its perceived effectiveness after crises such as COVID-19 and social unrest. Furthermore, it contextualizes these findings within the framework of ESRS, especially the social (S) dimension of the CSRD directive.Research methodology: Using a quantitative and qualitative approach, the study aims to identify shifts in managerial attitudes, communication structures, their responsibility and their contribution to fostering sustainability in times of uncertainty.Findings:  The findings emphasize the growing importance of structured internal communication—and coaching as one of its tools—as a means of cultivating personal and organizational responsibility, enhancing employee value, and fostering resilient, sustainable organizational cultures.Practical implications: The study contributes to theoretical understanding and provides practical guidelines for embedding coaching in communication strategies to support long-term organizational resilience.
Keywords: internal communication, coaching, sustainability, public relations, organizational resilience